A Case of Endobronchial Chondroma - Wada, Genji; Hanzawa, Suguru (The Japanese journal of thoracic diseases, 1985)
A case of benign lung tumor, chondroma, which developed in the left main bronchus is presented, and discussed with reference to the literature on this subject. The patient was a 27 year-old female who complained of cough and sputum. As an abnormal shadow was recognized on chest X-ray films, she had been treated for pneumonia. However, the incidence of symptoms became frequent and she was admitted to our hospital. A poorly-defined infiltrative shadow was disclosed in the left upper lung field on chest X-ray films, and bronchography and bronchoscopy revealed stenosis of the left main bronchus due to tumor. Biopsy and cytological examinations, however, did not show any findings suggestive of malignancy. An intrabronchial benign tumor was suspected, and left upper lobe lobectomy with sleeve resection of the left main bronchus was performed. Histologically, the tumor was diagnosed as chondroma which developed in the lumen of the left main bronchus. The postoperative course was uneventful and she is in good condition 36 months after surgery.